Evaluation of personality characteristics of Lithuanian inmates using the MMPI-2 - Laurinavičius, Alfredas; Laurinaitytė, Ilona; Ustinavičiūtė, Laura (Kriminologijos studijos, 2018)
[only abstract in English; full article and abstract in Lithuanian]The Minnesota Multiphasic Personality Inventory 2 (MMPI-2) is the most widely used self-report test used for screening of personality and psychopathology in a variety settings including forensic setting. The research in various populations of offenders confirms them possessing characteristics such as antisocial, lacking of impulse control, irresponsible, etc., and these characteristics are captured by the MMPI-2 scales. The goal of this study was to evaluate personality characteristics of incarcerated male and female offenders with the MMPI-2 and to analyse the results in light of results from other offender population studies. The finding of current study shows that the MMPI-2 characteristics of Lithuanian incarcerated offenders generally appear to be similar to those obtained in other cultural environments. Incarcerated offenders were best defined by higher Psychopathic Deviate (Pd), Paranoia (Pa), Antisocial Behavior (RC4), Ideas of Persecution (RC6), Discontraint (DISC), Overcontrolled Hostility (O-H), MacAndrew Alcoholism Revised (MAC-R) scales scores and lower scores of Ego Strength (Es) and Sociala Responsibility (Re) scales. This study has confirmed the results of earlier research and justified the MMPI-2 application for psychological assessment in Lithuanian offenders’ sample.
Keywords: MMPI-2, personality assessment, offenders